ETHICS AND ADVOCACY IN PSYCHIATRIC NURSING PRACTICE - Gail W. Stuart (Indian Journal of Psychiatric Nursing)
This paper explores the need for thoughtful consideration of ethics, ethical decision-making and ethical dilemmas in psychiatric nursing practice. Current realities in the field often create complex situations that can challenge the nurse's beliefs, values, emotions and actions - and ultimately compromise the quality of care delivered to the patient. Additionally, psychiatric nurses must be advocates for patients and engage in community and mental health advocacy activities that reflect both personal and professional commitments to the vulnerable population for whom they care.